Association between red blood cell distribution width and mortality in severe osteomyelitis patients - Yunlong Liu; Yan Zheng; Sheng Ding (Scientific Reports)
Abstract Red blood cell distribution width (RDW) is considered to be associated with the prognosis of patients with severe infections. This study aims to investigate the relationship between RDW and prognosis in osteomyelitis patients admitted to the ICU. Through a retrospective cohort study, relevant records of severe osteomyelitis patients were collected from the Medical Information Mart for Intensive Care (MIMIC-IV) database. Patients were divided into low-level and high-level groups based on the median RDW. The primary outcome was the one-year mortality rate of ICU patients. Univariate and multivariate Cox models were used to determine the relationship between RDW and mortality rate in osteomyelitis patients, with hazard ratios (HRs) and 95% confidence intervals (CIs) calculated. Kaplan–Meier survival curves were used to analyze patient survival status. Restricted Cubic Spline (RCS) was used to detect the nonlinear relationship between RDW and mortality rate. Stratified analysis was performed to explore the interaction between different subgroups. The study included a total of 1109 patients, among which 134 (12.08%) died within one year. Results from both univariate and multivariate Cox regression analyses indicated a significant association between elevated RDW levels (HR = 2.128, 95% CI 1.324–3.420) and an increased risk of mortality in patients with osteomyelitis. Kaplan–Meier survival curves demonstrated that the survival time of patients in the low RDW group was greater than that of those in the high RDW group (p < 0.0001). RCS analysis revealed a non-linear increase in the strength of the correlation between patient mortality rate and continuous changes in RDW. Subgroup analysis also observed a relationship between RDW levels and mortality rates in patients with osteomyelitis. Elevated RDW levels are correlated with an increased risk of mortality in osteomyelitis patients admitted to the ICU.